Electrospun cerium-based TiO2 nanofibers for photocatalytic oxidation of elemental mercury in coal combustion flue gas. (October 2017) - Wang, Lulu; Zhao, Yongchun; Zhang, Junying
Abstract: Photocatalytic oxidation is an attractive method for Hg-rich flue gas treatment. In the present study, a novel cerium-based TiO2 nanofibers was prepared and selected as the catalyst to remove mercury in flue gas. Accordingly, physical/chemical properties of those nanofibers were clarified. The effects of some important parameters, such as calcination temperature, cerium dopant content and different illumination conditions on the removal of Hg 0 using the photocatalysis process were investigated. In addition, the removal mechanism of Hg 0 over cerium-based TiO2 nanofibers focused on UV irradiation was proposed. The results show that catalyst which was calcined at 400 °C exhibited better performance. The addition of 0.3 wt% Ce into TiO2 led to the highest removal efficiency at 91% under UV irradiation. As-prepared samples showed promising stability for long-term use in the test. However, the photoluminescence intensity of nanofibers incorporating ceria was significantly lower than TiO2, which was attributed to better photoelectron-hole separation. Although UV and O2 are essential factors, the enhancement of Hg 0 removal is more obviously related to the participation of catalyst. The coexistence of Ce 3+ and Ce 4+, which leads to the efficient oxidation of Hg 0, was detected on samples. Hg 2+ is the final product in the reaction of Hg 0 removal. As a consequence, the emissions of Hg 0 from flue gas can be significantly suppressed. These indicate that combining photocatalysis technology with cerium-based TiO2 nanofibers is a promising strategy for reducing Hg 0 efficiently. Highlights: Cerium-based TiO2 nanofibers were successfully synthesized by electrospinning. Hg 0 photocatalytic oxidation was investigated over cerium-based TiO2 nanofibers. Roles of interferential gas components on Hg 0 removal were clarified. High removal efficiency of Hg 0 were observed for sample with 0.3% Ce. High stability of samples was observed for long-term use.